2009
DOI: 10.1016/j.mce.2008.11.012
|View full text |Cite
|
Sign up to set email alerts
|

The role of the brain in female reproductive aging

Abstract: In middle-aged women, follicular depletion is a critical factor mediating the menopausal transition; however, all levels of the hypothalamic-pituitary-gonadal (HPG) axis contribute to the age-related decline in reproductive function. To help elucidate the complex interactions between the ovary and brain during middle-age that lead to the onset of the menopause, we utilize animal models which share striking similarities in reproductive physiology. Our results show that during middle-age, prior to any overt irre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
88
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(91 citation statements)
references
References 111 publications
3
88
0
Order By: Relevance
“…Ključne reči: ženke pacova, srednje doba, hipofi zne će-lije, estradiol decrease in circulating estradiol, is a critical factor triggering the menopausal transition (6), along with the distinctive changes at the level of the hypothalamus and anterior pituitary hormone-producing cells in the same individuals (7)(8).…”
Section: Starenje Kod žEnskog Pola Je Biološki Proces Tokom Kojeg Dolmentioning
confidence: 99%
“…Ključne reči: ženke pacova, srednje doba, hipofi zne će-lije, estradiol decrease in circulating estradiol, is a critical factor triggering the menopausal transition (6), along with the distinctive changes at the level of the hypothalamus and anterior pituitary hormone-producing cells in the same individuals (7)(8).…”
Section: Starenje Kod žEnskog Pola Je Biološki Proces Tokom Kojeg Dolmentioning
confidence: 99%
“…The ovaries work under the control of the hypothalamicpituitary-gonadal (HPG) axis [16,17], which synchronizes the ovarian secretions with those of pituitary and placental hormones for stimulating breast development in preparation for milk production [17,18]. Primiparous women younger than 25 years of age who have elevated serum levels of hCG during their first trimester have 33% decreased risk of a breast cancer diagnosis after age 50, whereas estrogen concentrations have been positively associated with risk of breast cancer before age 40, supporting the role of this or other pregnancy hormones in the development of breast cancer [19][20][21][22][23].…”
Section: Pregnancymentioning
confidence: 99%
“…During these periods the maturation of the hypothalamic gonadal (HPG) axis [16,17,33] and endogenous hormone secretions play essential roles on the development of the breast at puberty, which is driven by the initiation of ovulation and the establishment of regular menstrual cycles [34]. The architecture of the breast of normally cycling women has been widely described as composed of three main lobular structures that are classified on the basis of their degree of development into lobules type 1 (Lob 1), lobules type 2 (Lob 2) and lobules type 3 (Lob 3) [22,35,36].…”
Section: The Human Breast In Pregnancy and Diseasementioning
confidence: 99%
“…Taken together, this suggests that the input onto GnRH neurons may change with age, resulting in less activated GnRH neurons and reduced GnRH release that together with a reduction in endogenous GnRH priming could indeed lead to an attenuated LH surge. Previous studies have proposed a contribution of the suprachiasmatic nucleus (SCN) in the attenuation of the LH release surge (Wise et al, 2002;Downs and Wise 2009). Yet, we did not find any significant changes in timing of the LH surge (i.e.…”
Section: Reproductive Aging and The Hypothalamusmentioning
confidence: 99%
“…The latter is strongly associated with the age at which rats become acyclic (Nass et al, 1984). Previous research suggested that changes in ovarian hormone release (DePaolo et al, 1986;Lu et al, 1985), pituitary hormone storage and/or responsiveness to ovarian or hypothalamic signaling (Brito et al, 1994;Keizer et al, 2001;Matt et al, 1998), or changes in hypothalamic signaling (Rubin et al, 2000;Downs and Wise, 2009;Wise et al, 2002) may underlie the age-related attenuation of the pituitary LH surge. Evidence suggests that exposure to chronically elevated levels of circulating E 2 during life advances the decline in fertility with age (Lu et al, 1981;Rodrigues et al, 1993).…”
Section: Introductionmentioning
confidence: 99%